Computational Investigation of Protein Photoinactivation by Molecular Hyperthermia - Kang, Peiyuan (J Biomech Eng, 2021)
To precisely control protein activity in a living system is a challenging yet long-pursued objective in biomedical sciences. Recently, we have developed a new approach named molecular hyperthermia (MH) to photoinactivate protein activity of interest without genetic modification. MH utilizes nanosecond laser pulse to create nanoscale heating around plasmonic nanoparticles to inactivate adjacent protein in live cells. Here we use a numerical model to study important parameters and conditions for MH to efficiently inactivate proteins in nanoscale. To quantify the protein inactivation process, the impact zone is defined as the range where proteins are inactivated by the nanoparticle localized heating. Factors that reduce the MH impact zone include the laser pulse duration, temperature-dependent thermal conductivity (versus constant properties), and nonspherical nanoparticle geometry. In contrast, the impact zone is insensitive to temperature-dependent material density and specific heat, as well as thermal interface resistance based on reported data in the literature. The low thermal conductivity of cytoplasm increases the impact zone. Different proteins with various Arrhenius kinetic parameters have significantly different impact zones. This study provides guidelines to design the protein inactivation process by MH.